Photodegradation of Methylene Blue with Aid of Green Synthesis of CuO/TiO2 Nanoparticles from Extract of Citrus Aurantium Juice - Shahnaz Bassim; Alyaa K. Mageed; Adnan A. AbdulRazak; Farooq Al-Sheikh (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
Green synthesis methods using plants have many advantages such as time-saving, chemical-free, and negative effects on the environment. So, extracted Citrus aurantium juice was used to synthesize green CuO/TiO2 and(G- CuO/TiO2) nanocatalyst which was characterized by XRD, SEM, EDX, FTIR, BET, and ZP and utilized in the degradation of methylene blue (MB) under UV lamps and dark environments. The ANOVA program was used to maximize the photodegradation efficiency (%) of (G-CuO/TiO2) on the MB dye. The four independent variables: Initial dye concentration (10-50 mg/L), pH (3-9), adsorbent dose (200-1000 mg/L), and contact time (30-90 min) served to the model of the photodegradation efficiency (%). The ANOVA results confirmed the high significance of the regression model while the predicted values of the photodegradation efficiency (%) of MB were in good agreement with the corresponding experimental ones. Optimized conditions for the maximum photodegradation efficiency (98.6%) by (G- CuO/TiO2) NPs were the initial dye concentration (10.93 mg/L), pH (8.87), adsorbent mass (986.43 mg/L), and contact time (89.08 min). The validity of the quadratic model was examined, and found in good agreement with the experimental values. Results demonstrated that (G-CuO/TiO2) could be a promising photocatalyst in the degradation of MB dye. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).